Catechol-O-methyltransferase rs4680 and rs4818 haplotype association with treatment response to olanzapine in patients with schizophrenia - Matea Nikolac Perkovic (Nature Portfolio, 2020)
Abstract Antipsychotic drugs target primarily dopaminergic system which makes catechol-O-methyltransferase (COMT) an interesting target in studies searching for treatment response predictors in schizophrenia. The study assessed the association of the COMT rs4680 and rs4818 polymorphisms with therapeutic response to olanzapine, risperidone, clozapine or other antipsychotic medication after 8 weeks of monotherapy in patients with schizophrenia. 521 Caucasian patients with schizophrenia received a monotherapy with olanzapine (10–20 mg/day; N = 190), risperidone (3–6 mg/day; N = 99), or clozapine (100–500 mg/day; N = 102). The fourth group (N = 130) consisted of patients receiving haloperidol (3–15 mg/day), fluphenazine (4–25 mg/day) or quetiapine (50–800 mg/day). Treatment response was defined as a 50% reduction from the baseline positive and negative syndrome scale (PANSS) total and subscale scores, but also as an observed percentage reduction from the initial PANSS0–6 total and subscale scores. Carriers of the COMT rs4680 A allele and carriers of the COMT rs4680–rs4818 C-A haplotype block had greater reduction in the PANSS total scores following olanzapine treatment, compared to carriers of the COMT rs4680 GG genotype and other COMT rs4680–rs4818 haplotypes. The COMT rs4680 A allele, and COMT rs4680–rs4818 C-A haplotype, were significantly associated with therapeutic response in patients treated with olanzapine, but not in patients treated with other antipsychotics.